Revision of the genus Miridiba Reitter, 1902 (Coleoptera, Scarabaeidae, Melolonthinae): genital morphotypes and new taxonomic data - Gao, Chuan-bu; Coca-Abia, María Milagro (European Journal of Taxonomy, 2021)
The genus Miridiba Reitter, 1902, of phytophagous chafers from Asia, is revised based on external morphological and genital (male and female) characters. In this study, a total fifty-eight species of Miridiba were examined, and the genus is redescribed. Male genital characters of Miridiba, especially the morphology of parameres and endophallus, are studied in depth herein. The female genitalia of Miridiba are studied and described in detail for the first time. According to genital characters, nine genital morphotypes, including fifty-four species, are established under the genus Miridiba. Sixty-seven type specimens are studied. Miridiba gressitti (Frey, 1970) comb. nov., Miridiba borneensis (Moser, 1918) comb. nov., Miridiba coxalis (Arrow, 1944) comb. nov., Miridiba rugaticollis (Moser, 1913) comb. nov., Miridiba nigrescens (Moser, 1916) comb. nov., Miridiba scutata (Reitter, 1902) comb. nov., Miridiba ciliatipennis (Moser, 1903) comb. nov. and Miridiba brunneipennis (Moser, 1916) comb. nov. are transferred from Holotrichia. Holotrichia dalatensis Frey, 1970 is transferred to Miridiba as a synonym of Miridiba sinensis (Hope, 1842). Four junior subjective synonyms are proposed: Miridiba pilosella (Moser, 1908) (= Holotrichia formosana Moser, 1909), Miridiba sinensis (= Holotrichia dalatensis Frey, 1970), Miridiba scutata (= Holotrichia scutulata Dalla Torre, 1912 and Miridiba lassallei Keith, 2010). Miridiba frontalis (Fairmaire, 1886) is resurrected as a valid species. A key to 51 of the 58 valid species of Miridiba is presented.